Realized evolvability: quantifying phenotypic evolution in a Drosophila clade - Yassin, Amir; Carareto, Claudia Marcia A. [UNESP]; Noll, Fernando Barbosa [UNESP]; Bicudo, Hermione Elly Melara de Campos [UNESP]; David, Jean R. (Wiley-Blackwell Publishing, Inc, 2011)
Understanding the evolutionary potential of morphological evolution is still a major problem in evolutionary biology. In this study, we tried to quantify the amount of variation of different traits among species of a Drosophila clade reared under standard conditions. Nineteen different traits have been measured on nine species of the same clade, the Neotropical saltans group of Drosophila. Measured traits can be distributed into five categories: size-traits (wing and thorax), shape indices (ratios among the size traits), number of sternopleural bristles on the thorax, number of abdominal bristles on successive sternites, and dorsal pigmentation of abdomen. All species are of medium size with a generally dark pigmentation. A remarkable feature is the presence of numerous bristles on the 6th sternite of the males, while this segment is bare in other Drosophila species. A multivariate analysis revealed that it was possible to discriminate all the investigated species by using the complete set of measured traits. For each trait, phenotypic variability was investigated at the within- and between-species levels. As a rule, the interspecific coefficient of variation (CV) was much greater than the within species CV, and it is proposed to call it realized evolvability. All possible correlations were calculated between traits across species, providing many unexpected results. Size traits were highly correlated among them, but not correlated with shape indices. Abdominal traits (bristles and pigmentation) were correlated, but often in opposite directions, with thoracic shape indices. Tergite pigmentation was negatively correlated with bristle number on sternite. For the moment, most of the correlations cannot be explained by developmental processes or parallel selective pressures. Nonetheless, mapping the evolution of the two characters on a molecular phylogeny of the studied species revealed two opposite phylogenetic trends for abdominal pigmentation and setation, respectively. Our data suggest a need for similar studies in other well-defined Drosophila clades.ResumeComprendre le potentiel evolutif des caracteres morphologiques constitue un probleme majeur de la biologie de l'evolution. Dans cet article, nous essayons de quantifier la variation de differents caracteres entre les especes d'un clade de Drosophilaelevees dans les conditions standard du laboratoire. Dix neuf traits differents ont ete mesures sur 9 especes appartenant au meme clade, le groupe saltans de Drosophila. Les caracteres mesures peuvent etre repartis en cinq categories: des caracteres de taille (aile et thorax) des indices de forme (rapports entre les caracteres de taille); le nombre de soies sternopleurales sur le thorax, le nombre des sois abdominales sur le sternites successifs et finalement la pigmentation des tergites. Toutes les especes sont de taille moyenne avec une pigmentation generale sombre. Une caracteristique remarquable est la presence de nombreuses soies sur le 6eme sternite des males, alors que ce segment est completement nu chez les autres especes de Drosophila. Une analyse multivariee a montre qu'il etait possible de discriminer toutes les especes etudiees en utilisant l'ensemble des caracteres mesures. Pour chaque trait, la variabilite phenotypique a eteetudiee aux niveaux intra et interspecifique. En regle generale, le coefficient de variation (CV) interspecifique etait beaucoup plus grand que le CV intraspecifique, et il est propose de l'appeler evolvabilite realisee. Toutes les correlations possibles entre les differents caracteres des especes ont ete calculees, conduisant souvent a des resultats inattendus. Les caracteres de taille sont fortement correles entre eux, mais non avec les indices de forme. Les caracteres de l'abdomen (soies et pigmentation) sont correles, mais souvent de facon opposee, avec les indices de forme. La pigmentation des tergites est negativement correlee avec le nombre des soies sur les sternites. Pour le moment, il ne semble pas possible d'explique la plupart des correlations par des processus de developpement ou bien par des pressions selectives paralleles. Cependant, la comparaison de deux caracteres avec le phylogenie moleculaire a revele des tendances phylogenetiques opposees concernant la pigmentation et la setation de abdomen. Ces resultats suggerent la necessite d'etudes comparatives similaires dans d'autres clades bien definis de Drosophila.
Keywords: Phylogenetic comparative method; body size; shape indices; bristle number; abdomen pigmentation; cladic analysis